Fuentes de financiamiento y su impacto en el desarrollo del sector microempresarial financiero del cantón La Maná, provincia de Cotopaxi - Chango Suntasig, Alexandra Abigail (2017)
The research was based on an analysis of the sources of financing and their impact on the development of the microenterprise financial sector in La Maná, Cotopaxi province. The methodology for the development of the objectives was formed by the types of research: bibliographical and descriptive, the methods applied were the inductive, deductive and analytical method in conjunction with the census technique.The results obtained from the representatives of the financial entities showed that the main characteristics of the sources of financing is that 50% of the financial institutions are financed by raising money from their partners from the items of deposits or savings and in terms of external financing in the case of the Savings and Credit Cooperatives, they opted to acquire loans in the “Corporación Financiera Nacional” and the banks that opted to acquire a loan came from international entities such as Vision Fund International; the indicators used for the analysis of business development were: the growth of human talent, segments to which they belong according to their assets, annual profitability and the level of efficiency and effectiveness in which it was determined that if there was an accelerated development of the financial sector . Finally, the calculation of the chi-square method was used to determine the incidence of financing sources in the development of financial institutions where the variables were applied: profitability, growth of human talent, efficiency levels, efficiency reflected values below the acceptance zone therefore it was determined that the sources of financing do not significantly affect the development of the financial sector.